Smoking and E-cigarettes Behaviour during COVID-19 Pandemic: A Scoping Review - Mohd Shaid, Lina Amirah; Omar, Mohd Rahman (International Journal of Human and Health Sciences (IJHHS), 2022)
Objectives: Smoking increases the risk for severe COVID-19 outcomes, which may reduce smoking activity among smokers. However, anxiety, stress, and boredom, especially during the lockdown, may increase cigarette consumption during COVID-19 pandemic despite the worrying complications. This study aimed to review the changes in tobacco smoking and electronic cigarette behaviour following the COVID-19 pandemic and to explore smoking cessation campaigns, programs, or promotions during this period. Methods: A search was conducted on EBSCOHOST and PubMed using keywords of (COVID-19 OR "Novel Coronavirus" OR "2019 novel coronavirus" OR 2019-nCoV OR SARS-CoV-2) AND ("Smoking behaviour*" OR "smoking cessation" OR "quit smoking" OR e-cigarette OR "electronic nicotine delivery systems" OR "electronic cigarette" OR vaporiser OR e-cigarette OR vaping). The inclusion criteria include articles in English language and reported on smoking behaviour and using electronic cigarettes during COVID-19, and any campaigns or support for smoking cessation within the timeline before, during and after the lockdown. Results: A total of 196 articles were screened. Upon completing inclusion and exclusion criteria, 35 articles were included in this review involving subjects aged 12 to 86 years. Among the articles, 25 had described changes in cigarette smoking behaviour. Most smokers did not significantly change their smoking behaviour during pandemics. However, about one-third of smokers reduced their cigarette smoking amount. Among the articles on e-cigarettes, 12 of them were reviewed. Most users did not reduce their e-cigarette consumption, while a study done in the USA had demonstrated a 44% reduction. Six papers had reviewed the support or programs for smoking cessation during COVID-19. There were increased programs for smoking cessation; most programs were conducted online, either on social media or using apps. Conclusion: With the growing concern and various actions of individuals and the community towards the pandemic, the authority should seize this chance to advocate smoking cessation by implementing strategies tailored to the current pandemic situation. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S44